Obstructive sleep apnea in asthmatic children: a cross-sectional study about prevalence and risk factors - Cristiane Fumo-; Anna K. Smith; Sonia M.G.P. Togeiro; Sergio Tufik; Gustavo A. Moreira (Elsevier, 2023)
Objectives: Primary objectives were to analyze the prevalence of obstructive sleep apnea in (1) boys and girls, and (2) severe asthma versus moderate and mild cases. The authors hypothesized that girls and severe asthma would have a higher prevalence of obstructive sleep apnea. Methods: Cross-sectional evaluation of asthmatic children attending a tertiary Pediatric Pulmonology clinic. The authors performed a history, physical examination, pulmonary function test, and home sleep apnea test. Results: The authors studied 80 consecutive patients, 7-18 years old, mean age of 11.6 years (standard deviation 2.7), 51.3% female, and 18.5% obese. Pulmonary function tests were obtained from 80 volunteers, 45% with obstruction pattern. Home sleep apnea tests were available from 76 volunteers, with a mean obstructive respiratory index of 1.8 events/h. Obstructive sleep apnea was found in 49 volunteers (61.2%). The authors did not find associations between obstructive sleep apnea and sex or asthma severity. Conclusions: Obstructive sleep apnea was frequent among these asthmatic children. Sex and asthma severity were not risk factors. Considering the interrelationship of both diseases, it is worth keeping in mind the possibility of obstructive sleep apnea among children and teenagers with asthma.